Differential response by tandem leaders and followers to landmark-rich and landmark-poor environments - Norasmah Basari; Ana B. Sendova-Franks; Alan Worley; Nigel R. Franks (Animal Cognition)
Abstract When animals use the same route repeatedly, they have the opportunity to update information that might help them to navigate more quickly and more accurately. Here we analyse ants involved in tandem running, in which the leader has evaluated a new nest and decided to recruit to it while the follower has chosen to be led and shown the route. We used a motorised gantry equipped with a camera to track the movements of tandem members on their tandem and return trips in a landmark-rich and a landmark-poor environment. Although the amount of visual navigational information did not affect the movements of leaders or followers on their tandem trip, the paths of followers were significantly more tortuous and their speeds significantly slower than those of leaders on their return trips in the landmark-poor environment. By contrast, there were no such differences between the followers and leaders on their return trips in the landmark-rich environment even though the return paths of followers in the landmark-rich environment were significantly more tortuous than that of leaders in the landmark-poor environment. Indeed, in the landmark-rich environment, the majority of the leaders’ return paths had loops while most were straight in the landmark-poor environment. Thus, the availability of more information when many landmarks are present may induce tandem leaders to make the loops, typically associated with the paths of tandem followers. This suggests knowledgeable individuals slow down to update navigational information and has implications for the formation of leader oligarchies in tandem running.